The wisdom of Thoth : magical texts in ancient Mediterranean civilisations - Bakowska-Czerner, Grazyna,; Roccati, Alessandro, 1941-; Świerzowska, Agata, (Archaeopress archaeology., 2015)
This volume represents a selection of contributions on Mediterranean themes from a wider international interdisciplinary conference on Magical Texts in Ancient Civilizations, organised by the Centre for Comparative Studies of Civilizations at Jagiellonian University in Krakow.